Refractive errors in type II diabetic patients - Shrestha, Shristi; Kaini, Khem Raj (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: The prevalence of diabetes is increasing rapidly. Refractive error in the diabetic population is considered a main cause of visual impairment. So this study was conducted to find out the pattern of refractive errors in patients with type II diabetes mellitus in Western Nepal.MATERIAL AND METHODS: It was a hospital-based cross-sectional study. Three hundred forty eyes of one hundred seventy patients with type II diabetes underwent comprehensive eye examination including subjective and objective refraction and serum biochemistry.RESULTS: The mean refraction was -0.132±0.88 D. Emmetropia was seen in 49.7% of the patients, hypermetropia in 22.6%, myopia in 12.6%, and astigmatism in 15% of the patients. Older age groups had more hypermetropic refractive error (p